Union of the Comoros : Interim Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2006)
The Union of the Comoros's Interim Poverty Reduction Strategy (PRGS) paper reports that the government's macroeconomic objectives under the PRGS framework entail preserving major economic equilibria. To increase control over government spending, the government intends to reduce the relative weight of the wage bill, manage the public debt efficiently, and rationalize government outlays. Reforms are under way, with World Bank support aimed at more efficient handling of the public debt and improving the quality of services provided in the context of a rehabilitation of public finance.